Scoping review of costs of implementation strategies in community, public health and healthcare settings - Hongmei Wang; Jungyoon Kim; Tzeyu L Michaud; Emiliane Pereira; Gwenndolyn Porter; Caitlin Golden; Jennie Hill; Cindy Schmidt; Paul A Estabrooks (BMJ Open)
Objectives To identify existing evidence concerning the cost of dissemination and implementation (D&I) strategies in community, public health and health service research, mapped with the ‘Expert Recommendations for Implementing Change’ (ERIC) taxonomy.Design Scoping review.Data sources MEDLINE, EMBASE, CINAHL, PsycINFO, Scopus and the Cochrane Library were searched to identify any English language reports that had been published between January 2008 and December 2019 concerning the cost of D&I strategies.Data extraction We matched the strategies identified in each article using ERIC taxonomies; further classified them into five areas (eg, dissemination, implementation, integration, capacity building and scale-up); and extracted the corresponding costs (total costs and cots per action target and per evidence-based programme (EBP) participant). We also recorded the reported level of costing methodology used for cost assessment of D&I strategies.Results Of the 6445 articles identified, 52 studies were eligible for data extraction. Lack of D&I strategy cost data was the predominant reason (55% of the excluded studies) for study exclusion. Predominant topic, setting, country and research design in the included studies were mental health (19%), primary care settings (44%), the US (35%) and observational (42%). Thirty-five (67%) studies used multicomponent D&I strategies (ranging from two to five discrete strategies). The most frequently applied strategies were Conduct ongoing training (50%) and Conduct educational meetings (23%). Adoption (42%) and reach (27%) were the two most frequently assessed outcomes. The overall costs of Conduct ongoing training ranged from $199 to $105 772 ($1–$13 973 per action target and $0.02–$412 per EBP participant); whereas the cost of Conduct educational meetings ranged from $987 to $1.1–$2.9 million/year ($33–$54 869 per action target and $0.2–$146 per EBP participant). The wide range of costs was due to the varying scales of the studies, intended audiences/diseases and the complexities of the strategy components. Most studies presented limited information on costing methodology, making interpretation difficult.Conclusions The quantity of published D&I strategy cost analyses is increasing, yet guidance on conducting and reporting of D&I strategy cost analysis is necessary to facilitate and promote the application of comparative economic evaluation in the field of D&I research.